The Influence of Organizational Culture and Work Environment on Employee Job Satisfaction (Study on UD Employees. Son of Ts Majalengka) - Cucu Irwanti; Dudung Abdullah; Pipih Sopiyan; Elin Herlina (Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
Job satisfaction is employee happiness at work and employee satisfaction in meeting their needs while working. The level of employee satisfaction can be influenced by organizational culture and work environment. The purpose of this research was to find out how the influence of organizational culture and work environment on job satisfaction (Study on Employees of UD Putra TS Majalengka). The research method used the descriptive verification method. The population in this study were all employees of UD Putra TS Majalengka with a total of 167 people. The saturated sampling technique was chosen as the sampling technique so that the total population as a whole was used as the research sample. The analytical method used in this study is multiple linear regression analysis, which is first tested by the instrument (validity and reliability), the classical assumption test, and the model feasibility test, which is then tested by the hypothesis. The results showed that partially organizational culture and work environment have a significant effect on job satisfaction. In this study, the work environment has a high influence on job satisfaction compared to organizational culture.